Determination of Phosphorus in Soil by ICP-OES Using an Improved Standard Addition Method. (13th September 2018) - Yang, Jing; Bai, Jingwen; Liu, Meiyu; Chen, Yang; Wang, Shoutong; Yang, Qiyong
Abstract : In this study, an improved standard addition method (ISAM) was developed for the determination of phosphorus in soil by ICP-OES based on the conventional standard addition method (CSAM) and calibration curve method (CCM). Certified standard soils were analyzed by the proposed ISAM method. The values obtained by ISAM method agreed with the certified values. Additionally, the results obtained by ISAM method were compared with those determined by the other two methods (CSAM and CCM). All the values obtained by the ISAM agreed with those from the other two methods. The detection limit, quantification limit, and recovery rate of each method were calculated, and the recovery rates of soil samples and the blank were all within the range of 90%–110%. Finally, the proposed method was applied to determine phosphorous in soil samples from Guangnan County, Yunnan Province, China, and the meadow soil from Qinghai-Tibet Plateau, China. The relative errors between the results from ISAM and CCM were all within 10%, and t -test showed that the results between ISAM and CCM had no significant difference (P > 0.05 ). Therefore, the proposed method overcame the matrix effect in some extent and was an acceptable method for the rapid and accurate batch analysis of P content in soil sample, especially batch samples with obvious matrix effect.